Integration of Local Wisdom of "Tabe" Culture in Character Education-Based Learning at Elementary Schools in Makassar City - Lutfi; Herawati Syamsul; Fachruddin Aziz; Akhmad Kurnia; Muhammad Wajdi (Didaktika: Jurnal Kependidikan, 2024)
The "tabe" culture has an influence in shaping students' character and is relevant to apply in everyday life both in the family and school environment. Its philosophical values ​​must be maintained through integration in character education-based learning. Thus, integrating "tabe" culture in learning will strengthen students' character and identity. This research uses a qualitative approach, namely ethnographic research, to observe the application of "tabe" culture in character education in the school environment. The data obtained were analyzed using the Miles and Huberman model. The research results showed that the application of "tabe" culture in elementary schools in Makassar city is currently starting to be abandoned by the majority of students, this is due to students' lack of understanding of the application and meaning of "tabe" culture. However, the cultivation of character education has been integrated into subjects and extracurricular activities at school. The integration of "tabe" culture in character education must require commitment and support from various parties, including schools, teachers, students, parents and the community. Apart from that, it must require careful planning, consistent implementation, and planned evaluation.